2018
DOI: 10.1080/0284186x.2018.1502467
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of advanced radiotherapy approaches using photon techniques and particle therapy in the postoperative management of thymoma

Abstract: Background: The purpose of this study was to compare dosimetric differences related to target volume and organs-at-risk (OAR) using 3D-conformal radiotherapy (3DCRT), volumetric modulated arc therapy (VMAT), TomoTherapy (Tomo), proton radiotherapy (PRT), and carbon ion radiotherapy (CIRT) as part of postoperative thymoma irradiation. Material and methods: This single-institutional analysis included 10 consecutive patients treated with adjuvant radiotherapy between December 2013 and September 2016. CT-datasets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
1
22
1
Order By: Relevance
“…There is a substantial body of evidence from in silico comparative planning studies across a broad range of tumour sites comparing dose distributions between photon RT and PT demonstrating superiority in regard to normal tissue sparing. [2][3][4][5][6][7]44,[81][82][83] Proponents of PT view these data as indicating that PT will become the treatment of choice for specific indications once its availability is wide enough, in part for its compliance with the generally agreed As Low As Reasonably Achievable (ALARA) principle.…”
Section: Planning and Dosimetric Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…There is a substantial body of evidence from in silico comparative planning studies across a broad range of tumour sites comparing dose distributions between photon RT and PT demonstrating superiority in regard to normal tissue sparing. [2][3][4][5][6][7]44,[81][82][83] Proponents of PT view these data as indicating that PT will become the treatment of choice for specific indications once its availability is wide enough, in part for its compliance with the generally agreed As Low As Reasonably Achievable (ALARA) principle.…”
Section: Planning and Dosimetric Evidencementioning
confidence: 99%
“…1 When compared to photon RT, PT delivers radiation dose at least as conformally to the target volume, but allows better sparing of nearby and more distant organs at risk, as well as allowing for dose escalation. [2][3][4][5][6][7] As of the end of 2018, over 220,000 patients have been treated with PT worldwide. 8 Ninety-five PT centres (13 offering CIT alone or with PBT, the remainder PBT alone) are operational across Europe, Asia, the United States of America (USA) and Africa with another 66 centres under construction or in planning stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of thymoma, Haefner et al conducted dosimetric comparison between photon and particle radiotherapy in the postoperative management of thymoma. The results revealed that particle radiotherapy showed superior organs at risk sparing and optimal target volume coverage (48). However, up to now, no data were reported about the implementation of particle radiation in induction radiation of thymoma.…”
Section: What's the Role Of Radiation Technology Advances In Thymoma?mentioning
confidence: 99%
“…To date, there have been no reports of both effects in one patient, even with photon or proton irradiation. Carbon-ion radiotherapy is a form of heavy-ion radiation modality with stronger effects on tumor cells by physical dose (higher relative biological effect) and better dose distribution compared with photon-based therapies[ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%